Menkes kinky hair disease (Menkes syndrome) - Fister, Petja (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2006)
Menkes disease (MD) is a rare genetic neurodegenerative disorder. It is causedby a mutation in the ATP7A gene, which codes for the copper-transporting ATPase in the cell organelles. Dysfunction of many copper-dependent enzymes results in low concentrations of copper in some tissues and accumulation of copper in others. We report on a boy that at the age of 2 months presented with encephalopathy with epileptic seizures and later had a progressive developmental disorder. Despite treatment with variousantiepileptic drugs, some seizures still persisted. Our diagnosis was made on the basis of clinical and laboratory findings. We also plan to confirmthe diagnosis genetically. To the best of our knowledge, this is the first reported case of MD in Slovenia. Treatment of MD is usually not successful, especially in sporadic cases, because it usually begins too late. Early neonatal treatment may be successful in half of the cases.
Keywords: genetske bolezni; lasje; neurology; nevrodegeneracija; nevrologija